Atmospheric Impacts of Oil Well Blowouts: A Synergistic Assessment Using Satellite Remote Sensing and WRF-Chem Modeling - Jhuma Biswas; Bijit Kumar Banerjee; Chandrakala Bharali; Barlin Das; Binita Pathak; Pradip Kumar Bhuyan (Journal of the Indian Society of Remote Sensing, 2026)

Simultaneous conversion of chromium and malachite green coexists in halophilic bacterium Halomonas xianhensis SUR308 isolated from a solar saltern - Jhuma Biswas; Himadri Sekhar Sarkar; Amal Kanti Paul; Sukhendu Mandal (Environmental Science and Pollution Research, 2023)

Reduction of hexavalent chromium by a moderately halophilic bacterium, Halomonas smyrnensis KS802 under saline environment - Jhuma Biswas; Pritha Bose; Sukhendu Mandal; A. K. Paul (Environmental Sustainability, 2018)

Satellite‐retrieved direct radiative forcing of aerosols over North‐East India and adjoining areas: climatology and impact assessment - Jhuma Biswas; Binita Pathak; Falguni Patadia; Pradip K. Bhuyan; Mukunda M. Gogoi; S. Suresh Babu (International Journal of Climatology, 2017)

Satellite‐retrieved direct radiative forcing of aerosols over North‐East India and adjoining areas: climatology and impact assessment - Jhuma Biswas; Binita Pathak; Falguni Patadia; Pradip K. Bhuyan; Mukunda M. Gogoi; S. Suresh Babu (International Journal of Climatology, 2017)
In order to understand the climatic implications of atmospheric aerosols, top of atmosphere ( TOA ) shortwave ( SW , 0.3–5 µm) fluxes and aerosol optical depth ( AOD ) at 550 nm retrieved simultaneously by clouds and the earth's radiant energy system ( CERES ) and moderate resolution imaging spectroradiometer ( MODIS ) instruments, respectively, are analysed over North‐East India and its adjoining areas for the period July 2002–December 2013. The aerosol‐free TOA flux obtained by establishing the linear regression between CERES SW TOA fluxes and MODIS AODs exhibits strong seasonality with peak values in monsoon and minimum in winter. Same seasonality is captured by the Santa Barbara DISORT Atmospheric Radiative Transfer ( SBDART ) model, but with difference in absolute values. SBDART code is used to extend instantaneous radiative forcing estimates into 24‐h averages. AOD over the North East India region with complex terrain shows altitudinal variation with maximum value at the lowest elevation site Dhaka and minimum value at the high‐altitude locations Shillong and Aizwal. In general, strong seasonality in AOD is observed with a peak in pre‐monsoon (March–May) and dip in post‐monsoon (October–November) at all the locations. The direct instantaneous TOA shortwave aerosol radiative forcing ( SWARF ) shows maximum values in pre‐monsoon over all the locations except at Guwahati, Banmauk, Aizawl, and Shillong. The lowest value of instantaneous SWARF is observed in post‐monsoon except at Banmauk and Shillong. Climatologically TOA diurnally averaged SWARF varies between −6.95 W m −2 in Aizawl to −20.39 W m −2 in Shillong. In general, the TOA SW forcing efficiency is highest in monsoon at all the locations. The radiative forcing efficiency is found to be less negative when surface reflectance increases.

Partial characterization of an extracellular polysaccharide produced by the moderately halophilic bacterium Halomonas xianhensis SUR308 - Jhuma Biswas; J. Ganguly; A.K. Paul (Biofouling, 2015)

Alterations in enzyme activities in vital organs of triploid female catfish Heteropneustes fossilis (Bloch) - Angshuman Biswas; Mitali Pramanik; Samita Kundu; Sumedha Roy; Jhuma De; Arun Kumar Ray (Fish Physiology and Biochemistry, 2006)